THE INFLUENCE OF ACCOUNTING INFORMATION SYSTEMS, AUDIT QUALITY AND KNOWLEDGE ON THE ACCURACY OF AUDIT OPINION (CASE STUDY: ACCOUNTING FIRM IN MEDAN CITY) - Sartika Siagian, Dewi; Thezar Fiqih Hidayat Hasibuan; Nuzullina, Sari (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the effect of accounting information systems, audit quality and knowledge partially on the accuracy of audit opinion provision at Public Accounting Firms in Medan. The sample selection method in this study was carried out using purposive sampling. The sample was taken as many as 45 respondents from a total population of 244 auditors working at 20 Public Accounting Firms in Medan. The independent variables in this study are accounting information systems (X1), audit quality (X2) and knowledge (X3), while the dependent variable is the accuracy of audit opinion provision. Data analysis used multiple linear regression analysis. The results of the study indicate that the Accounting Information System has a significant effect on the accuracy of audit opinion provision at Public Accounting Firms in Medan. Audit quality has a significant effect on the accuracy of audit opinion provision at Public Accounting Firms in Medan. Knowledge has a significant effect on the accuracy of audit opinion provision at Public Accounting Firms in Medan. Accounting Information Systems, audit quality and knowledge simultaneously have a significant effect on the accuracy of audit opinion provision at Public Accounting Firms in Medan.